Pendidikan Islam dan Penguatan Moderasi Beragama: Peran dan Tantangan dalam Konteks Global - mohammad yahya; Halim Soebahar; Moh. Chotib; Muhammad Noor Harisuddin (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
This research aims to examine the role and challenges of Islamic education in strengthening religious moderation through a literature review. The main focus of the research is to explore how Islamic education can contribute to strengthening religious moderation amidst increasingly complex global dynamics. Based on literature analysis, it was found that Islamic education plays an important role in building tolerance, respecting differences, and promoting peace. However, its implementation in various countries faces challenges, such as extremism and a narrow understanding of religion. This research concludes that Islamic education must be updated to respond to the challenges of globalization and encourage more inclusive and universal religious moderation